Literature Review: Identifying the Potential of Smartwach Technology in Health - Rangkuty, Meis Putri; Asti, Rahma Dwi; Br. Ginting, Radha Agri; Dalimunthe, Nadiyah Rahma; Purba, Sri Hajijah (PROMOTOR, 2025)
Health is a very important aspect in our lives. Because a healthy body is the main asset so that we can carry out various daily activities without problems. Therefore, we must always try to maintain a healthy body. Smartwatches are in the health sector. Smartwatches not only function as accessories, but are also equipped with sensors that enable real-time monitoring of health conditions, such as heart rate, oxygen saturation and physical activity. With advances in technology, smartwatches are transforming into wearable health devices, supporting disease prevention and health maintenance. The method used in this research is SPIDER-based literature observation (Sample, Phenomenon of Interest, Design, Evaluation, Research Type) collecting and analyzing 5 articles from 24,840 relevant articles. The results show that smartwatches can contribute to preventive health monitoring, and have the potential to promote a healthy lifestyle. This research emphasizes the importance of technology integration in improving society’s welfare.